ANALISIS KELAYAKAN EKONOMI DAN VALUASI DAMPAK BANJIR TERHADAP MASYARAKAT DI KABUPATEN PATI - M Miftahul Munir; Rosalina Kumalati; Ellyn Normelani (Pelantar Press, 2025)
This study aims to analyze economic feasibility and assess the impact of flooding on communities in Pati Regency, an area with a high level of vulnerability to hydrometeorological disasters. The approach used is a descriptive-analytical method with Benefit-Cost Ratio (B/C), Net Present Value (NPV), and Social Return on Investment (SROI) calculations based on secondary data from government agencies and the results of socio-economic surveys of the affected communities. The results of the study show a B/C value of 1.21, a positive NPV of IDR 17.8 billion, and an SROI of 1.6, which means that every IDR 1 of public investment in flood control generates social benefits worth IDR 1.60. The analysis shows that flood mitigation efforts through the construction of embankments, drainage improvements, and community education are economically and socially feasible. These results emphasize the importance of an environmental economic approach in disaster risk management in flood-prone areas such as Pati Regency.